Actors and politics in Finland’s forest-based bioeconomy network - Korhonen, Jaana; Giurca, Alexandru; Brockhaus, Maria; Toppinen, Anne (2018)
Abstract: To foster innovativeness for supporting (forest-based) bioeconomy development, participation in decision-making and interaction between diverse actors become a necessary precondition for designing and implementing transition policies. However, who forms the emerging policy networks, and which policy beliefs are promoted? Based on data from a national online survey, we performed a quantitative social network analysis to investigate emerging social structures and policy beliefs in the context of the Finnish forest-based bioeconomy. Our explorative analysis shows that research, governmental, and industrial organizations mainly constitute the Finnish forest-based bioeconomy network. Actors primarily exchange information, and most key organizations report high levels of trust among each other. However, the network structure is rather closed. This raises concerns about equal benefit sharing and the inclusiveness of concerned actors. We discuss the implication of this network structure for enabling new innovations. Finally, we present the key aspects and drivers of “business as usual”, and suggest an option for or a more transformative change in the Finnish forest-based bioeconomy